Chapter 5. Evelyn Briggs Baldwin and Operti Bay - Lockerby, Amanda (Septentrio Conference Series, 2015)
During the second Wellman polar expedition, to Franz Josef Land in 1898, Wellman’s second-in-command, Evelyn Briggs Baldwin, gave the waters south of Cape Heller on the northwest of Wilczek Land the name ‘Operti Bay.’ Proof of this is found in Baldwin’s journal around the time of 16 September 1898. Current research indicates that Operti Bay was named after an Italian artist, Albert Operti. Operti’s membership in a New York City masonic fraternity named Kane Lodge, as well as correspondence between Baldwin and Rudolf Kersting, confirm that Baldwin and Operti engaged in a friendly relationship that resulted in the naming of the bay.